Implementation of Psychomotor Assessment and Teacher Readiness in Islamic Religious Education Learning at Senior High Schools in Bandung City - Syifa Nurjamilah Fatwa Fadilah; Saepul Anwar; Risris Hari Nugraha (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to explore the implementation of psychomotor assessment in Islamic Education (PAI) learning at a public senior high school in Bandung City. The research employed a qualitative approach with an instrumental case study design, utilizing interviews, observations, and document analysis. Data were analyzed through the stages of reduction, presentation, and conclusion drawing. The findings indicate that teachers conceptualize psychomotor assessment as the evaluation of authentic worship skills. Assessment planning was grounded in curriculum achievements with analytic rubrics that emphasized performance indicators, while implementation combined direct observation, video portfolios, and performance tasks to capture reliable evidence of student competence. Assessment results were used for formative feedback, remedial activities, and enrichment, whereas teacher professional development was conducted through MGMP forums, practical training, and continuous self-initiated efforts. This study is limited to a single school context, thus the findings cannot be broadly generalized. Recommendations include rubric standardization across schools, ongoing practical training, and the utilization of digital portfolios to enhance reliability, accountability, and the educational impact of psychomotor domain learning.